2006
DOI: 10.1681/asn.2006050423
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Localization and Expression of Angiotensin-Converting Enzyme 2 and Angiotensin-Converting Enzyme

Abstract: Angiotensin-converting enzyme 2 (ACE2) expression has been shown to be altered in renal tubules from diabetic mice. This study examined the localization of ACE and ACE2 within the glomerulus of kidneys from control (db/m) and diabetic (db/db) mice and the effect of chronic pharmacologic ACE2 inhibition. ACE2 co-localized with glomerular epithelial cell (podocyte) markers, and its localization within the podocyte was confirmed by immunogold labeling. ACE, by contrast, was seen only in glomerular endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
500
5
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(578 citation statements)
references
References 40 publications
37
500
5
23
Order By: Relevance
“…The high expression of ACE2 in the normal kidney (2) and the reduced expression of ACE2 in diabetic rats (16) and human kidney diseases (17,18) suggest an ACE2 involvement in diabetic nephrology. To explore the renoprotective effects of ACE2, most investigators have focused on ACE2 inhibition and demonstrated that ACE2 deficiency aggravated glomerular injury in mice (19)(20)(21). A recent study found that intraperitoneal injection of human recombinant ACE2 slowed the progression of diabetic nephropathy in diabetic mice, although exogenous proteins may cause immunity reaction after injection, which shortens its half-life (22).…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of ACE2 in the normal kidney (2) and the reduced expression of ACE2 in diabetic rats (16) and human kidney diseases (17,18) suggest an ACE2 involvement in diabetic nephrology. To explore the renoprotective effects of ACE2, most investigators have focused on ACE2 inhibition and demonstrated that ACE2 deficiency aggravated glomerular injury in mice (19)(20)(21). A recent study found that intraperitoneal injection of human recombinant ACE2 slowed the progression of diabetic nephropathy in diabetic mice, although exogenous proteins may cause immunity reaction after injection, which shortens its half-life (22).…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistencies can be found in mouse glomerular ACE2 presence as described even by the same group. 28,29 Besides, kinetic differences in AngI and AngII metabolism are shown to be exist between rat, human and sheep kidneys. 25,30,31 There are some limitations to our study.…”
Section: Controlsmentioning
confidence: 99%
“…Thus, Ang 1-7 has become a key component of the RAS system due to its beneficial effects in the cardiovascular system. Although the pathophysiological significance of ACE2 in renal injury remains to be established, emerging evidence suggests that ACE2 deficiency leads to increases in intrarenal Ang II levels (Ribeiro Oliveira Ferrario, 2006;Oudit et al;Wolf & Ritz, 2005;Ye et al;2006). Thus, recently ACE2 has also been proposed as an acute biomarker of renal disease, considering that upregulation of ACE2, and the subsequent increase in Ang 1-7 levels, may be a compensatory response to protect against tissue injury.…”
Section: Ace2mentioning
confidence: 99%